Between Meccan Origins and Medinan Expansion: A Diachronic Reading of Secondary Embedding in Qs. Al-Muddaththir [74]: 31 - Muhammad Tajuddin; Muh. Awaluddin A; Bambang Sampurno; Basyir Arif (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2025)
This study examines the phenomenon of secondary embedding in the Qur’an, understood as the incorporation of Medinan material into surahs of Meccan provenance through a process of intra-textual development during the prophetic period. The case under consideration is Qs. al-Muddaththir [74]:31, a verse whose exceptional length constitutes a marked statistical departure from the otherwise compact rhythmic pattern of the surah. Drawing on Nicolai Sinai’s analytical framework and the principle of structural cohesion, this article argues that when the verse is analytically bracketed as a distinct literary layer, the thematic continuity of the surrounding passage remains intact, no discernible narrative gap emerges, and the surah’s overall rhythmic and structural balance is preserved. It is further proposed that the motive underlying this embedding is responsive in character, the verse appears to address dialogical concerns arising from the early audience’s engagement with the Qur’anic proclamation, while the phrase fī qulūbihim maraḍ aligns terminologically with vocabulary characteristic of the Medinan discursive context. This study contributes to the growing scholarly conversation on the dynamic textual development of the Qur’an, particularly as it pertains to surah structure and its relationship to the evolving social and theological horizons of the early Muslim community. It further offers a methodological contribution to the diachronic study of surah composition, demonstrating how structural and terminological analysis may illuminate the Qur’an’s responsive engagement with its formative historical context.